2017
DOI: 10.1111/aec.12482
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of native grasses and their impact on exotic annuals in degraded box gum woodlands

Abstract: Restoration goals often involve the addition of new species to resident, degraded communities but in box gum woodlands such restoration is often constrained by competition from persistent exotic annuals that control critical ecological processes. Nutrient reduction (via carbon addition) and seed bank depletion are two approaches to reduce competition from exotic annuals but to be effective these treatments must allow establishment of species such as native grasses. This experiment was conducted in two degraded… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 58 publications
(191 reference statements)
0
12
0
Order By: Relevance
“…The correlations between soil properties and plant biomass do indicate that a reduction in soil nutrients could be a contributing factor to the overall success of TSR. However, when C was added in an attempt to reduce nutrients, we found a reduction in biomass of both weeds and native plants even though soil nutrients became comparable to similar native grasslands (Prober et al 2005; Cole et al 2017). Therefore, it is likely other factors, or a combination of factors, result in TSR being successful.…”
Section: Discussionmentioning
confidence: 63%
“…The correlations between soil properties and plant biomass do indicate that a reduction in soil nutrients could be a contributing factor to the overall success of TSR. However, when C was added in an attempt to reduce nutrients, we found a reduction in biomass of both weeds and native plants even though soil nutrients became comparable to similar native grasslands (Prober et al 2005; Cole et al 2017). Therefore, it is likely other factors, or a combination of factors, result in TSR being successful.…”
Section: Discussionmentioning
confidence: 63%
“…The presence of key C4 grass species that regulate ground layer diversity and provide resilience to weed invasion (Cole et al . 2017 and references therein) and the presence of resprouting ‘characteristic’ woodland eucalypt tree species support that BGW is a functionally distinct community across seven bioregions with distinct landscape and climate configurations (Fig. 2 and see Thackway & Cresswell 1995).…”
Section: Methodsmentioning
confidence: 75%
“…We attempted to overcome this delay by planting mature tubestock plants rather than using direct seeding. Therefore, our native grasses would have been more developed than those in the study by Cole et al (2017) who found that Austrostipa (C3 species) swards with successful recruitment of C4 grasses, including T. triandra, suppressed exotic annuals more than the Austrostipa-only. Alternatively, the climatic conditions may not have favoured the C4 species and thus have made them less competitive.…”
Section: C4 Native Plants Were Not Strong Competitorsmentioning
confidence: 83%
“…Alternatively, the climatic conditions may not have favoured the C4 species and thus have made them less competitive. For example, these species may depend on summer rains to become established or build up their individual tussock sizes (Cole et al, 2017;Lodge, 1981), whereas our site had below average rainfall over the summer (we watered to the average rainfall to aid establishment). In addition, the very wet spring of 2016 (200 mm above average; Figure 2) may have provided ideal conditions for the C3 plants (native and exotic) and given them a competitive edge over the C4 species.…”
Section: C4 Native Plants Were Not Strong Competitorsmentioning
confidence: 99%